2011
DOI: 10.1111/j.1346-8138.2011.01413.x
|View full text |Cite
|
Sign up to set email alerts
|

Nestin‐positive hair follicle pluripotent stem cells can promote regeneration of impinged peripheral nerve injury

Abstract: Nestin-positive, keratin 15 (K15)-negative multipotent hair follicle stem cells are located above the hair follicle bulge. We have termed this location the hair follicle pluripotent stem cell area. We have previously shown that transplantation of nestin-expressing hair follicle stem cells can regenerate peripheral nerve and spinal cord injuries. In the present study, we regenerated the impinged sciatic nerve by transplanting hair follicle pluripotent stem cells. Human hair follicle stem cells were transplanted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 23 publications
2
36
0
5
Order By: Relevance
“…Differentiation into epithelial and vascular cells emphasizes the important role HFSCs have in vascularizing the skin and dermis [130][131][132] . A small number of studies have reported the use of undifferentiated HFSCs in murine models of sciatic and tibial nerve crush and transection injuries [133][134][135] . HFSCs were found to differentiate into glial fibrillary acidic protein positive SC-like cells and participated in myelination.…”
Section: Skin Derived Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentiation into epithelial and vascular cells emphasizes the important role HFSCs have in vascularizing the skin and dermis [130][131][132] . A small number of studies have reported the use of undifferentiated HFSCs in murine models of sciatic and tibial nerve crush and transection injuries [133][134][135] . HFSCs were found to differentiate into glial fibrillary acidic protein positive SC-like cells and participated in myelination.…”
Section: Skin Derived Precursorsmentioning
confidence: 99%
“…The expression of leukemia inhibitory factor and insulin-like growth factor has also been detected [8] . These factors are thought to improve neuronal survival, promote corticospinal tract growth, [133] Mouse sciatic crush U Culture medium…”
Section: Culture Mediummentioning
confidence: 99%
“…Він складається з концентрич-но розташованих циліндрів, що містять клітини, які продукують високоспеціалізовані протеїни, зокрема, кератин, основний компонент волосся і перебувають у постійному динамічному стані: фаза росту (анаген), перехідна фаза (катаген), фаза спокою (телоген). МСК-ПНГ розташовані у зоні потовщення піхви во-лосяного мішечка (bulge of hair follicles) у точці при-кріплення к м'язу -підіймачу є волосина (m. arrector pili) [21].…”
Section: Abstract: Peripheral Nerve Injury; Autoneuroplasty; Tissue Eunclassified
“…Група вчених під керівництвом M. Sieber-Blum відкрили їх у 2004 р. і довели походження цих клі-тин з нервового гребеня [21]. Сьогодні доведено, що МСК-ПНГ, виділені з волосяного мішечка, можуть диференціюватися у нейрони, гліальні клітини, ос-теобласти, гладеньком`язові клітини, меланоцити in vitro [20,23] та демонструють цей мультилінійний по-тенціал на клональному рівні [24].…”
Section: Abstract: Peripheral Nerve Injury; Autoneuroplasty; Tissue Eunclassified
See 1 more Smart Citation